Taming the young and restless—epigenetic gene regulation in pancreas and beta-cell precursors - Russ, Holger A (EMBO J, 2014)
The in vivo assessment of epigenetic changes during mouse pancreatic beta-cell differentiation reveals surprising differences to directed, in vitro differentiation of human embryonic stem cells. New findings reported in this issue of The EMBO Journal further identify Ezh2 as a critical determinant of endocrine progenitor number and could instruct improved protocols for stem cell-based therapies.